Penerapan Kurikulum 2013 Dalam Peningkatan Kemampuan Belajar Aqidah Akhlak Siswa Kelas Vii - Fatimah Ahmad; Zaifatur Ridha (LPPM Institut Nasional Laa Roiba Bogor, 2019)
The purpose of this study was to obtain data on the implementation of the 2013 curriculum, whether it has been implemented well enough and has been applied for a long time at Al-Jamilah Sei Mati Private MTs Padang Tualang by involving students actively in learning and applying various learning methods. Teachers always try to innovate in managing learning by applying interesting methods and positioning themselves as facilitators according to the mandate of the 2013 curriculum. The principle of learning is to humanize humans (humanism), by nurturing children to grow cognitive, affective, psychomotor, life skills. social and spiritual. This research uses research with qualitative data approach in the data collection process and is described by describing the data obtained at the research location to the conclusion. As for the results of the research on educating with the ngemong system which is a form of guidance carried out by teachers to their students which is applied in madrasas. The students' ability to learn aqidah akhlaq has improved quite well with the implementation of the 2013 Curriculum, which can be seen from the active role of students when learning and student involvement during class discussions. Students' understanding of learning also increases which can be seen from the fairly good student scores and the application of religious values ​​that have been studied, especially in students of aqidah akhlaq. Students show good morals in the Madrasa environment both to teachers and to fellow friends.